Droplet Exposure Risk to Providers From In‐Office Flexible Laryngoscopy: A COVID‐19 Simulation. (18th August 2020) - Ye, Michael J.; Sharma, Dhruv; Rubel, Kolin E.; Lebo, Nicole L.; Burgin, Sarah J.; Illing, Elisa A.; Ting, Jonathan Y.; Moore, Michael G.; Yesensky, Jessica A.; Mantravadi, Avinash V.; Sim, Michael W.
Abstract : To provide data on risk of respiratory droplets from common otolaryngologic procedures during the COVID‐19 pandemic, a novel simulation of droplet exposure from flexible laryngoscopy was performed. After completion of a nasal symptom questionnaire, topical fluorescein spray was administered into the nasal and oropharynx of 10 healthy volunteers, who then underwent flexible laryngoscopy under 2 conditions: routine without provoked response and with prompted sneeze/cough. After each, droplets on the proceduralist and participant were counted under ultraviolet A light. Droplets were observed on 1 of 10 volunteers after routine laryngoscopy and 4 of 10 during laryngoscopy with sneeze/cough. A nasal symptom score based on congestion and rhinorrhea was significantly elevated among droplet producers after sneeze/cough ( P =. 0164). No droplets were observed on the provider. Overall, with adequate personal protective equipment, flexible laryngoscopy poses minimal droplet risk to providers. Nasal symptoms can identify patients more likely to produce droplets after sneeze/cough.